Homophonic Pun Generation with Lexically Constrained Rewriting. - Yu, Zhiwei; Zang, Hongyu; Wan, Xiaojun (Empirical Methods in Natural Language Processing, 2020)
Punning is a creative way to make conversation enjoyable and literary writing elegant. In this paper, we focus on the task of generating a pun sentence given a pair of homophones. We first find the constraint words supporting the semantic incongruity for a sentence. Then we rewrite the sentence with explicit positive and negative constraints. Our model achieves the state-of-the-art results in both automatic and human evaluations. We further make an error analysis and discuss the challenges for the computational pun models.